Perbandingan Ekspor Kopi Dua Pemasok Utama Dunia Indonesia dan Brazil: Sebuah Analisis Ekonomi Data Panel 2001 - 2006 - Wulandari, Indah Sri (Unisia, 2012)
International trading plays an important role in driving the economy of a country. The international trading through export activity enables a country to gain benefi ts such as foreign exchange, broader in house product market and also other benefi ts. Therefore, it represent one of he backbones of he economy of a country. One of the sectors that play an important part in the export activity of Indonesia is agriculture. Coffee is one of the important commodities of the sector. It is necessary to conduct a study of the Indonesian coffee export in order to improve it. The study of the internal factors infl uencing the Indonesian coffee export performance is required by examining the demand function of the Indonesian coffee export by the importing countries. Additionally, it is also necessary to study the competition between Indonesia and its competitor countries in international market and Brazil is determined as the competitor because the country is constantly on the fi rs rank as the coffee suppliers in the international market. It is expected that such a comparison enables Indonesia to gain more knowledge in developing and improving its coffee export.